No vazio, caberiam casas, parques, fábricas... caberia muita cidade - Nascimento, Agnaldo da Silva [UNESP] (2014)
The research aims to hold a discussion about urban space, with emphasis on urban voids, questioning this element contribution in the urban form structuring from two medium cities - Presidente Prudente (SP) and Londrina (PR), Brazil. First it’s considered these urban elements existence, maintenance and multiplication, are included in urban landscape, have been indicative of the cities production due to capital reproduction, at the answer of a less unequal city that favors life social point of view. Thus, the research will target the urban expansion in Presidente Prudente and Londrina, Brazil and the urban voids proliferation, considering the agents, who act and benefit from these cities territorial dispersion. Through a comparative study, aims to understand how the shapes, actions and urban dynamics are developed for this element production (urban void). So, from an assessment of the distinguishing characteristics from each city, as well as their commonalities, will explain this movement, know in part, and to understand the permanence of these void areas dynamics and implications for cities and urban life. Lastly, the research want contribute to urban planning actions, from the quantification and systematization of a database about urban voids in both cities, with the objective to improving the relevant information for decision making of managers, but also for society be aware of these elements that play an important role in urban morphology